The face of illusory truth: repetition of information elicits affective facial reactions predicting judgments of truth [dataset] - Stump, Annika; Wüstenberg, Torsten; Rouder, Jeffrey N.; Voß, Andreas (Universität, 2025)
People tend to judge repeated information as more likely being true compared to new information. A key explanation for this phenomenon, called the illusory truth effect, is that repeated information can be processed more fluently, causing it to appear more familiar and trustworthy. To consider the function of time in investigating its underlying cognitive and affective mechanisms, our design comprised two retention intervals. 75 participants rated the truth of new and repeated statements 10 minutes as well as 1 week after first exposure while spontaneous facial expressions were assessed via electromyography. Our data demonstrate that repetition results in specific facial reactions indicating increased positive affect, reduced mental effort, and increased familiarity (i.e., relaxations of musculus corrugator supercilii and frontalis), and subsequently increases the probability of judging information as true. The results moreover highlight the relevance of time: both repetition-induced truth effect and EMG activities decrease significantly after a longer interval. (2023-12-19)